Personal Networks and Elections in a Divided Society - Desi Rahmawati; Wegik Prasetyo; Elvira Marlien Marantika (PCD Journal, 2021)
Research on electoral politics in post-conflict societies tends to understand religious primordiality as a key factor driving voters' electoral preferences and voting behaviour. Such studies, despite their ability to explain fragmentation, ignore the role of personal networks in electoral consolidation. Those studies that do consider personal networks, at least in a Southeast Asian context, tend to highlight patronage and kinship politics. This paper aims to underscore the importance of personal networks within the context of a post-conflict society while also enriching studies of women and elections. Using the 2019 legislative elections in Ambon, Indonesia, as its case study, this article discusses the reasons, forms, and effectiveness of candidates' use of their personal networks. Although it rarely results in electoral victory, this strategy goes beyond the mere consolidation of constituents and votes. Women candidates' personal networks, which stem from their social, economic, and political activities, provide them with important avenues to approach unfamiliar communities and penetrate psychological barriers. In a divided society, where candidates prioritise offline campaign activities targeting particular communities, the presence of personal networks is crucial. In this sense, the strategies of electoral democracy—including personal networks—can contribute to peacekeeping.